2005
DOI: 10.1038/sj.ijo.0803122
|View full text |Cite
|
Sign up to set email alerts
|

Depressive mood and obesity in US adults: comparison and moderation by sex, age, and race

Abstract: Objective: Sustained depressive mood is a gateway symptom for a major depressive disorder. This paper investigated whether the association between depressive mood and obesity differs as function of sex, age, and race in US adults after controlling for socio-economic variables of martial status, employment status, income level and education level. Methods: A total of 44 800 nationally representative respondents from the 2001 Behavioral Risk Factor Surveillance Survey were studied. Respondents were classified as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
216
4
6

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 276 publications
(244 citation statements)
references
References 22 publications
18
216
4
6
Order By: Relevance
“…26 There is evidence for an increased prevalence rate of mental disorders, in particular depression, in treatmentseeking obese patients, whereas the findings concerning Mental disorders in patients with obesity in comparison with healthy probands H Baumeister and M Härter obese individuals from community samples are, as yet, inconsistent. [7][8][9][10][11][12][13][14]27 Obese individuals show a high current (4-week), 12-month and lifetime prevalence rate of comorbid mental disorders, irrespective of the underlying setting. In comparison with physically healthy probands, prevalence rates of obese individuals are significantly increased.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…26 There is evidence for an increased prevalence rate of mental disorders, in particular depression, in treatmentseeking obese patients, whereas the findings concerning Mental disorders in patients with obesity in comparison with healthy probands H Baumeister and M Härter obese individuals from community samples are, as yet, inconsistent. [7][8][9][10][11][12][13][14]27 Obese individuals show a high current (4-week), 12-month and lifetime prevalence rate of comorbid mental disorders, irrespective of the underlying setting. In comparison with physically healthy probands, prevalence rates of obese individuals are significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…The findings concerning the association of obesity and mental disorders are more inconsistent. Of eight recent epidemiological studies, six found increased prevalence rates of mental disorders, [7][8][9][10][11][12] whereas two did not. 13,14 However, despite their strengths, these studies have several shortcomings, which restrict their results.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 A growing body of evidence has shown that obesity, highly prevalent and increasing in the United States and worldwide, [4][5][6] is associated with an increased risk of developing psychiatric disorders. [7][8][9][10][11][12][13][14][15] However, most of the earlier studies failed to evaluate the effects of obesity-related comorbidities (ORCs), lifestyle factors (such as smoking, alcohol drinking and physical activity) or other psychosocial factors (such as general health status, emotional support and life satisfaction) on mental health simultaneously, although these factors also affect mental health status 13,[16][17][18][19] or are associated with mental disorders. 16,[20][21][22][23][24][25] On the other hand, some other studies have found no relationship 26 or an inverse association of overweight/obesity with mental disorders in men.…”
Section: Introductionmentioning
confidence: 99%